A New Turn in Russian Ethnography: Science and Cultural Politics at Moscow's First Ethnographic Exhibition of 1867. Issue 2 (1st September 2022) - Kerimova, Mariam M.; Zolotukhina, Maria V.
Abstract: The article is based on the text analysis of previously unknown archival documents (letters, petitions) to assess the impact of Pervaa Vserossiiskaya etnographicheskaya vystavka (the first all-Russian ethnographic exhibition) had on different spheres of Russian life – ranging from reinterpreting Slavic identity and rallying Western and Southern Slavs around the empire to growing museum attendance. Demonstrating the diversity of ethnic groups in Russia, in addition to emphasising its imperial power managed to also serve the purpose of structuring and further developing academic knowledge, and presenting its results to the larger public in an easily accessible yet sophisticated way: the Ethnographic Department of the Imperial Society of Devotees of Natural Science, Anthropology and Ethnography at Moscow University was founded in 1868, and the first ethnographic museum (Dashkov Museum) in Moscow used the items for its collection. Russian ethnography exercised this new chance of proclaiming itself as an independent and actively evolving discipline and field of knowledge.